Ramdarash Mishr Ke Kavya Me Chhand Yojana: An analysis of Chhand Yojana in Ramdarash Mishr's poetry (Journal of Advances and Scholarly Researches in Allied Education, 2012)
^NUn* 'kCn dk vFkZ dks"k esa vkYgknu Hkh gS1 &¶NUn vkYgkn;frbfr NUn%¸ vFkkZr~ tks euq";ksa dks izlUu djrk ;k vkuUn nsrk gS] og NUngSAvkpk;Z jkepUnz 'kqDy us rks Li"V 'kCnksa esa fy[kk gS fd ^dfork dk iwjklkSUn;Z NUn dks y; ds lkFk tksj ls i